Research on thermal comfort of obese and overweight people during indoor running exercise - Zhou, Haixia; Xie, Dong; Xiao, Peilin (Building and environment, 2023)
Regular and adequate physical exercise plays a pivotal role in enhancing physical fitness, mitigating the occurrence of obesity, and upholding body weight. The comfort of individuals engaging in exercise is significantly impacted by various environmental factors within sports fields, including ambient temperature, humidity, air velocity, and mean radiant temperature. To investigate the influence of ambient temperature, relative humidity, and body mass index (BMI) on the comfort levels of individuals with high body fat during exercise, treadmill running experiments were conducted within controlled environmental chambers. Furthermore, the subjects’ subjective sensations and physiological indexes were recorded. The results implied that subjects exhibited a broader range of acceptable thermal sensations during exercise compared to rest periods. Moreover, individuals with a higher BMI displayed heightened sensitivity to elevated temperatures and a greater propensity for perceiving sensations of heat, resulting in a narrower range of acceptable exercise conditions. Additionally, the findings highlighted that air temperature exerted a more pronounced impact on comfort levels than humidity. For indoor running exercises, it was advisable to maintain ambient temperatures within the ranges of 15.1°C–24.3 °C and 16.1°C–27.8 °C for obese and overweight individuals, respectively. Furthermore, it was recommended to maintain a relative humidity level between 50% and 80% in the exercise environment. •The thermal comfort of obese and overweight people during running was studied.•The effects of temperature, humidity and BMI on comfort during running were studied.•Recommended temperature and humidity for obese and overweight people were obtained.•A new method of measuring MST during running by infrared imager was explored.